(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Due to the lack of consensus on what kind of pregnancy should be considered post-term, there are very conflicting data in the literature on the frequency of post-term pregnancy. However, according to most authors, the frequency of postmaturity ranges from 1.4 to 14%, averaging 10% [1, 8]. A description of post-term pregnancy is already found in ancient treatises dating back to the era of Hippocrates and Galen. The beginning of a scientific approach to this problem dates back to 1902, when Ballantyne and then Runge (1948) first described signs of overmaturity in a newborn, and this syndrome was called Bellentyne-Runge syndrome. Despite such a solid history, many issues regarding this pathology have not yet been resolved [2, 10].